O pessoal é político: conscientização feminista e empoderamento de mulheres - Sardenberg, Cecília Maria Bacellar (2018)
The personal is political: feminist consciousness-raising and women’s empowerment ABSTRACT In the history of women’s movements, feminist consciousness raising and action groups, as well as gender awareness workshops have - and continue to have - a fundamental role in the destruction of patriarchy. In this work, I intend to recover some of this history, to think about the relevance of these spaces of consciousness raising and collective action for the empowerment of women today. To do so, I begin with a discussion of different approaches to power and women’s empowerment, with emphasis on approaches that emphasize consciouness-raising processes and collective action. Keywords: Women’s empowerment. Feminist consciousness-raising groups. Consciousness-raising and collective action. Feminist movement. Women’s liberation movement.